As metamorfoses de rede de poder agroindustrial sucroalcooleira no Estado de São Paulo: da regulação estatal para a desregulação - Mello, Fabiana Ortiz Tanoue de (Universidade Federal de São Carlos, 2004)
Since the thirties, the sugar-cane section from São Paulo expanded as a policy network, where the industrialists, sugar-cane suppliers and the state interests were orchestrated. However, after the section deregulation process, happened along the nineties, deep transformations have been happening in these actors interests and in their power relations, delineating a new governance structure in this agroindustry of the state of São Paulo. This work has as main objective to identify these transformations, analyzing the configuration of the new structure of power that is formed after the removal of the state of the section regulation arenas. Starting from the study of the present actors characteristics in this network (number of participants; type of interest of the members; participants function in the network) and their relationship (articulation type; centricity; stability and frequency of the interaction; distribution of the power resources and the public participants strategies), it was possible to verify that the network formed during the Proálcool operation period - where the wide availability of resources in the hands of the state, made possible the coordination of the network to this actor - it became a power network where the interests of the state, of Unica and Orplana are orchestrated in the process of elaboration of the sugar-cane politics. In this governance structure that is formed after the nineties, the new state position led the industrialists and sugar-cane suppliers from São Paulo to an adaptation process, changing their action strategies, organization forms and representation of their interests. The most specific proposal of this work is to identify the main challenges for the section to reach selfmanagement. In this context, it was possible to conclude that the sugar-cane actors from São Paulo demonstrate a poor effort (enforcement) to consolidate or to improve the way of an effective governance, adopting opportunist attitudes that just seek short-term results and linking with little frequency and speed in some subjects of the section (mainly when the theme is the regulation of the sugar-cane supply and its by-products). Therefore, the results obtained in this research enlarge the knowledge of relationship established among the productive actor of this agroindustry of great importance for the Brazilian economy
Keywords: Política agrícola; Rede de poder; Regulação agrícola; Governança; Setor sucroalcooleiro; Enforcement; Network; Regulation; Governance; Power sugar-cane; Enforcement; ENGENHARIAS::ENGENHARIA DE PRODUCAO